Restoration by recolonization of native species seeding in semiarid rangelands of Patagonia (Semiárida, 2023)
A. In the Magellan Steppe of south Patagonia, degradation of Festuca grasslands leads to dwarf shrub steppes in an irreversible way, but a secondary succession following a disturbance such as plowing and seeding may aid the restoration. We studied degraded Festuca gracillima grasslands (Fg site) and Lepidophyllum cupressiforme shrublands in salty nitric soils (MVsite) that had been plowed, seeded, and seasonally grazed thereafter with sheep. The pastures (100-500 ha) were: recent (1 year in Fg and 7 yrs in Mv), intermediate (11 yrs), and old (16 yrs). Vegetationwas assessed using 3 500-point transects in each pasture and 0-20 cm soil samples were obtainedand analyzed in a laboratory. A Canonical Correspondence analysis using soil and vegetationproperties arranged transects of the Fg site according to age since sowing, but this did not happen inMv. In Fg introduced Agropyron sp. and Dactylis glomerata dominated initially but grasses and nativeforbs were recruited subsequently (Poa spiciformis, Deschampsia patula and Carex andina) and finallysome psamophyle grasses were incorporated (Pappostipa chrysophylla and Pappostipa ibarii). Coverand diversity were partially recovered in this relatively short time, showing that these semiaridrangelands retain resilience and restoration potential after a disturbance
Keywords: secondary succession; disturbance; seeding; Agropyron sp; biodiversity